Keefektifan Penggunaan Strategi CT-RAS (Creative Thinking-Reading Activities) terhadap Kemampuan Membaca Pemahaman pada Siswa Kelas XI SMA Negeri 1 Ngaglik - Arvianto, Faizal (FKIP Universitas Muhammadiyah Sukabumi, 2016)
This research is aimed at investigating the different ability of comprehensive reading between students who have obtained CT-RAs strategy learning and those who do not have in the grade XI of SMA N 1 Ngaglik. Furthermore, it aims to find out the effectiveness of CT-RAs strategy in the learning of comprehensive reading of grade XI students of SMA N 1 Ngaglik. This research used quasi-experimental method with pretest-posttest control group design. Cluster random sampling was used to pick sample groups, i.e. XI IPS 3 as the control group and XI IPA 1 as the experiment group. The data was collected by using tests. The instrument of the research was validated by using content validity and construct validity. Content validity was applied to find out the feasibility of the instrument. Construct validity was done by consulting the instrument to an expert (expert judgment). The reliability of the instrument was calculated by using alpha in the iteman program, and 0,853 was obtained. The date was analyzed by using t-test with 5 % level of significance. The result of analysis requirement showed that the pretest and posttest scores were in normal and homogeneous distribution. According to the t-test analysis of the posttest data of comprehensive reading of control group and experiment group, t score 0f 7,729 was obtained with df = 66 and p = 0,000. The p value was smaller than the 5 % level of significance. This result showed that there was a significant difference between students from control group and those from experiment group. The result of t-test analysis of the control group was 0.258 with df = 31 and p = 0,798. The p value was greater than the 5 % level of significance (0.798 > 0.05). Meanwhile, the t-test result of the experiment group was 14.758 with df = 35 and p = 0.000. The p value was smaller than the 5 % level of significance (0.000 < 0.05). This result showed that CT-RAs strategy was effective to be used in the learning of comprehensive reading in the grade XI of SMA N 1 Ngaglik.